Pathobiology of ALK-negative anaplastic large cell lymphoma - Pileri, Stefano A. (PAGEPress Publications, 2011)
The authors revise the concept of ALK-negative anaplastic large cell lymphoma (ALCL) in the light of the recently updated WHO classification of Tumors of Hematopoietic and Lymphoid Tissues both on biological and clinical grounds. The main histological findings are illustrated as well as the phenotypic, molecular and clinical characteristics. Finally, the biological rationale for possible innovative targeted therapies is presented.